Human CD8+CD28− T Suppressor Cells Expanded by IL-15 In Vitro Suppress in an Allospecific and Programmed Cell Death Protein 1-Dependent Manner - Feng, Fu; Liu, Yanjun; Liu, Guihuan; Zhu, Ping; Zhu, Manman; Zhang, Hua; Lu, Xiao; Liu, Jiumin; Luo, Xunrong; Yu, Yuming (Frontiers in Immunology, 2018)
CD8+CD28- T suppressor cells (Ts) have been recently documented to play an important role in alloimmunity. Therefore, understanding and optimizing the conditions under which these cells are generated and/or expanded would greatly facilitate further research and potential clinical use. In this study, we describe rapid expansion of human allospecific CD8+CD28- Ts cells through coculture of CD8+ T cells with HLA mismatched donor APCs plus IL-15 in a relative short period of time in vitro. Interestingly, IL-15 promotes the expansion of CD8+CD28- Ts cells through several parallel mechanisms. The expanded CD8+CD28- Ts cells up-regulate expression of CD132, CD25 and PD-1, but down-regulate expression of CD122, GZM-B and perforin, while exhibiting no cytotoxicity. Most importantly, the expanded CD8+CD28- Ts cells vigorously inhibit CD4+ T cells proliferation in a contact-dependent and donor-specific manner both in vitro and in vivo. Interestingly, the co-inhibitory molecules PD-1 and PD-L1 play an obligatory role in the mechanisms of CD8+CD28- Ts cells suppression. Taken together, our study report novel methodology for IL-15-induced expansion of human CD8+CD28- Ts cells and possible mechanisms. These findings may facilitate understanding of transplant rejection, and promote clinical application of CD8+CD28- Ts cell-based strategies for inducing and monitoring transplant tolerance in the future.